(untitled) (Bangladesh Journal of Medical Science, 2016)
Background: It is important to understand factors that influence choice of specialty among medical residents. Aim and objectives: The purpose of this study was to determine factors that influence residents decision for choice of specialty. A cross-sectional study was conducted in 2012-2013 and comprised 473 medical residents in Ahvaz Jundishapur University of Medical Sciences, Iran. A self-administered questionnaire was prepared after extensive literature review, piloted and distributed to all medical residents from different hospitals at the school of medicine. Results: 418 of 473 questionnaires were returned (response rate: 88.4%). The most important reasons for the choice of specialty were personal development and to provide better service with mean 4.31 of 5.0 and Personal Interests with mean 4.16, followed by Helping peoples and health promotion, Income and social Prestige and Easiness and being comfortable with mean values; 3.96, 3.59 and 2.44, respectively. We observed a difference in attitudes of men and women in term of the easiness and comfortability of specialty course. The mean values this factor was higher in women than in men (2.61 vs. 2.25, p=0.01). The findings revealed personal development and to provide better services, personal interests, helping people and health promotion are major motivating factors for the selecting a specialty. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.111-117